The Concept of Non-Conviction Based Asset Forfeiture As a Legal Policy in Assets Criminal Action of Corruption - Muhammad Fuad Azwar R; M. Said Karim; Haeranah (LEGAL BRIEF, 2022)
This research aims to analyze the legal regulations against mechanism of assets confiscation that exist in Indonesian positive law as well as to analyze the concept of non-conviction based asset forfeiture as a legal policy in assets ccriminal action of corruption. The type of research that used is normative (legal research) or doctrinal. The results of this research shows that asset confiscation regulations in indonesia’s current positive law carried out by handling criminal forfeiture and civil forfeiture but the regulations still based on criminal evidence first (follow the suspect) and criminal law still places the seizure of assets as an additional crime. Indonesia has ratified the United Nations Convention Against Corruption (UNCAC 2003) through law no. 7 of 2006 which then as a follow-up to the government in the renewal step publishes the draft law on the confiscation of assets for criminal actions which is expected to be the beginning of the asset seizure regime by focusing on efforts to return the assets (follow the money) where UNCAC as an international instrument proposes ratifying countries to apply the concept of asset forfeiture without relying depends on the sentencing of the perpetrator (non-conviction based asset forfeiture) as an effort to eradicate criminal action of corruption. The NCB concept is an effective solution to maximize the return of state losses through foreclosure and taking over of an asset in rem or lawsuit against assets as a form of criminal law policy.